Towards the development of core competencies for residency training coordinators of family medicine in the Philippines - Laude. Teri-Marie P. (Journal of Human Ecology, 2016)
This descriptive study was conducted to formulate a framework towards the development of core competencies for the role of family medicine Residency Training Coordinators (RTCs) in the Philippines. Initial data was obtained from participants using a cross-sectional survey. Delphi were conducted among experts to obtain a consensus on the RTC competencies. Content analysis was done. Results showed that all respondents are aligned with the Philippine Academy of Family Physicians (PAFP) setting the RTC qualification to be at least a dipmate, active member and in good-standing. As the head of the residency training committee, the RTC needs to balance personal and professional attributes-assertiveness, fair judgement, trustworthiness and ethical while evaluating residents and providing counsel. They have identified their training needs to be in organizational management and administration. The study showed that the role of the RTC is complex and identified the core competencies of RTC as manager or administrator, clinical teacher, evaluator, educational planner, and researcher. The final competency framework developed for family medicine RTCs follows the competency-based curriculum (CBC) track. It is most appropriate for RTCs as it sets the acceptable standard where professionals will be evaluated and clarifies the set of expectations focused on professional development programs and drives assessment of performance of RTCs. Training institutions can thus use the proposed framework as a guide in selecting, training, and evaluating the RTCs.